The Outcome of Vitrectomy in Macular Hole at Cipto Mangunkusumo National General Hospital - Andi Arus Victor; Eko Hadi Waluyojati; Ari Djatikusumo; Elvioza Elvioza; Gitalisa Andayani; Anggun Rama Yudantha; Mario Marbungaran Hutapea (International Journal of Retina, 2021)
Introduction: This study aims to determine the anatomical and functional outcomes in patients with macular hole (MH) underwent vitrectomy with internal limiting membrane (ILM) peeling. Method: A descriptive retrospective study at Vitreoretinal Division of Ophthalmology Department, Faculty of Medicine Universitas Indonesia – Cipto Mangunkusumo National General Hospital (FKUI-RSCM). Secondary data obtained from medical records of patient with MH within January – December 2017. The anatomical outcome was observed from the closure of MH. Functional outcome was observed from post-operative visual acuity at day-1, month-1, month-3, and month-6. Results: 16 patients who met the criteria were included in this study. MH closure was observed in 43.8% of cases and failed closure in 56.2%. Improvement of visual acuity was observed on closure cases in 3 months and 6 months, occurred in 71.43% and 100% of cases, respectively. Conclusion: MH closure rate was 43.8%. Satisfying result of improvement in visual acuity achieved after vitrectomy with ILM peeling.